Quantitative Multi-Parameter Mapping Optimized for the Clinical Routine - Cooper, Graham; Hirsch, Sebastian; Scheel, Michael; Brandt, Alexander U.; Paul, Friedemann; Finke, Carsten; Boehm-Sturm, Philipp; Hetzer, Stefan (Frontiers in Neuroscience, 2020)
Using quantitative multi-parameter mapping (MPM), studies can investigate clinically relevant microstructural changes with high reliability over time and across subjects and sites. However, long acquisition times (20 minutes for the standard 1-mm isotropic protocol) limit its translational potential. This study aimed to evaluate the sensitivity gain of a fast 1.6-mm isotropic MPM protocol including post-processing optimized for longitudinal clinical studies. 6 healthy volunteers (35±7 years old; 3 female) were scanned at 3.0T to acquire the following whole-brain MPM maps with 1.6 mm isotropic resolution: proton density (PD), magnetization transfer saturation (MT), longitudinal relaxation rate (R1), and transverse relaxation rate (R2*). MPM maps were generated using two RF transmit field (B1+) correction methods: 1) using an acquired B1+ map and 2) using a data-driven approach. Maps were generated with and without Gibb’s ringing correction. The intra-/inter-subject coefficient of variation (CoV) of all maps in the gray and white matter, as well as in all anatomical regions of a fine-grained brain atlas, was compared between the different post-processing methods using Student’s t-test. The intra-subject stability of the 1.6-mm MPM protocol is 2-3 times higher than for the standard 1-mm sequence and can be achieved in less than half the scan duration. Intra-subject variability for all four maps in white matter ranged from 1.2-5.3% and in gray matter from 1.8-9.2%. Bias-field correction using an acquired B1+ map significantly improved intra-subject variability of PD and R1 in the gray (42%) and white matter (54%) and correcting the raw images for the effect of Gibb’s ringing further improved intra-subject variability in all maps in the gray (11%) and white matter (10%). Combining Gibb’s ringing correction and bias field correction using acquired B1+ maps provides excellent stability of the 7-minute MPM sequence with 1.6 mm resolution suitable for the clinical routine.